An Impact of self-assessment budgetary program on budget decisions in Korea - KIM, Jisu (KDI School, 2018)
This paper aims to investigate the impact of Self-assessment Budgetary Program (SABP), a representative assessment tool of the public budgetary program in Korea. Multivariate analysis was conducted, focusing on 401 assessed budgetary programs in 2015 that were matched with budget data of FY 2014-2016, while controlling for the program characteristics and political content. The result shows the statistically significant impact of SABP on the budget decision. In particular, this impact is stronger when the program’s budget size is initially large or middle rather than small. Although planning and management evaluation components have statistically significant to outcomes, the result component does not. Also, the impact of planning component is much bigger than management component. Therefore, this performance evaluation system and its management, the evaluation process should be improved in order to reflect the real performance of the program.
Thesis(Master) --KDI School:Master of Development Policy,2018